2005
DOI: 10.1007/s00223-004-0048-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Osteoprotegerin/RANKL System, Bone Mineral Density, and Bone Biochemicals Markers in Patients with Recent Spinal Cord Injury

Abstract: This study analyzed the temporal and regional variations in bone loss and explored bone cell activities via biochemical markers during an extended follow-up in patients with spinal cord injury (SCI). In parallel, the possible role of the osteoprotegerin (OPG)/RANKL system in disuse osteoporosis was investigated. Seven male patients with acute and complete SCI (31.3 +/- 9.5 years) and 12 able-bodied (AB) men (26.9 +/- 4.2 years) participated in the study. Measurements were performed 16, 24, 36, 48, and 71 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
59
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 32 publications
8
59
2
2
Order By: Relevance
“…Spinal cord injury (SCI) has wide-ranging psychological and pathological effects, these last including an increase in bone resorption, [1][2][3] hormonal alterations [4][5][6] and modification of body composition. 7,8 The annual incidence of SCI differs according to the source but ranges from approximately 28.5 to 40 cases per million population.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Spinal cord injury (SCI) has wide-ranging psychological and pathological effects, these last including an increase in bone resorption, [1][2][3] hormonal alterations [4][5][6] and modification of body composition. 7,8 The annual incidence of SCI differs according to the source but ranges from approximately 28.5 to 40 cases per million population.…”
Section: Introductionmentioning
confidence: 99%
“…loss, 11,15,16 especially in young adults. 17 During the first months postinjury, demineralization occurs exclusively in the sublesional areas and predominantly in weightbearing skeletal sites such as the distal femur and proximal tibia, which are trabecular-rich sites, 3,11,15,18,19 while the diaphyseal areas of the femur and the tibia, which are cortical-rich sites, are relatively spared. 19 Using the dual energy X-ray absorptiometry (DEXA) technique, Wilmet et al 7 reported a decrease in bone mineral content (BMC) during the first year postinjury of about 4% per month in areas rich in trabecular bone and 2% per month in areas containing mainly cortical bone.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although well studied, 7,[11][12][13] there is conflicting evidence about the efficacy of electrically evoked muscle activation in the stimulation of bone metabolism (bone formation and/or reduction of bone loss), and the clinical role of functional electrical stimulation (FES) in the treatment of osteoporosis resulting from neurological damage. The reason for this conflict may be that bone metabolic abnormalities may be time dependent [14][15][16] or as-yet-unexplained factors affect the osteogenic response to mechanical strain. Alternatively, as it is well known that exerciseinduced bone effects are mode and dose dependent, and the exercise modes or doses used and/or tolerated by the patient with SCI may have been subtherapeutic.…”
Section: Introductionmentioning
confidence: 99%